Fitter Fontans for future—Impact of physical exercise on cardiopulmonary function in Fontan patients - Weigelt, Annika; Fritsch, Regina; Rottermann, Kathrin; Wällisch, Wolfgang; Moosmann, Julia; Dittrich, Sven; Purbojo, Ariawan; Schöffl, Isabelle (Frontiers in Cardiovascular Medicine, 2022)
Background In Fontans, exercise tolerance is poorer compared to their healthy peers. Higher V˙O2peak represents a strong predictor for mortality and morbidity in these patients. Cardiac rehabilitation programs have been shown to improve cardiopulmonary function in Fontans. More habitual physical activity should therefore lead to a better exercise tolerance. Methods We performed cardiopulmonary exercise testing in 24 Fontan patients who had engaged in physical activity for a minimum of 3 h per week over their lifetime. As a control we performed cardiopulmonary exercise testing in 20 Fontan patients who had undertaken no physical activity or <3 h per week in the past. Results A total of 44 Fontan patients was included (mean age 18.1 years). The mean parameters measured at peak exercise differed significantly between the active and inactive group (peak oxygen uptake [V˙O2peak] of 34.0 vs. 25.0 ml/min/kg, peak heart rate (HR) of 169.8/min vs. 139.8/min). Even though the O2pulse and the EF did not differ significantly between both groups, N-Terminal-Pro-B-Type Natriuretic Peptide (NT-pro BNP) was significantly higher in the inactive group. The two groups did not differ with respect to their cardiac function determined by magnetic resonance imaging (MRI). V˙O2peak was positively correlated with hours of sports performed by Fontans. Conclusions V˙O2peak and maximum HR were significantly higher in Fontans who had been physically active compared to those who had been inactive. The values reported in this study were higher than in other studies and reached normal values for V˙O2peak for most Fontans in the physically active group. The positive correlation between V˙O2peak and physical activity is an indicator of the importance of incorporating physical exercise programs into the treatment of Fontan patients.